Characteristics and Management of Drainage Infrastructure in Medan Sunggal District, Medan City - Hartini, Mira Ismilia; Nuraini, Cut; Milanie, Feby; Abdiyanto, Abdiyanto; Sugiarto, Abdi (International Journal Papier Advance and Scientific Review, 2023)
Climate change, characterized by high-intensity rainfall, coupled with inadequate drainage systems, small and shallow river dimensions, and a lack of community awareness, has caused flooding and inundation in Medan Sunggal District. This study aims to understand the characteristics and management of drainage infrastructure in Medan Sunggal Subdistrict, Medan City, to identify its characteristics and implement suitable management efforts. The research adopts a positivism paradigm with a positivistic approach, relying on empirical facts (sensual empiricism). The research methodology used is purely qualitative descriptive, focusing on an in-depth understanding related to the characteristics, context, and research subjects. Data collection methods include Guest Tour and comparative techniques. The results of this study show that the characteristics of drainage infrastructure in the study area form a network pattern. The types of channels in the study area are primary channels, secondary channels, and tertiary channels. They consist of artificial channels with open concrete construction, located above the ground with a combined drainage system. While most of the physical conditions are good, some exhibit minor damage. A significant portion of the drainage water is stagnant. Flood-prone areas constitute 41%, areas with infrequent flooding are at 43%, and areas that have never experienced flooding are at 16%. Management recommendations for the study area include providing green open spaces, creating biopore infiltration holes, constructing detention and retention ponds, using paving blocks/grass blocks, conducting maintenance (normalization and rehabilitation) of drainage, and involving the community in each management aspect.